Table expansion - Anas Basri, Musthafa (2009)
This report presents the additional table that serves as a table that has a larger surface area for table arm chair. Students often use tables arm chair, but table is usually in the design space with a limited surface. It is often used, especially in the classroom and lecture halls. In addition, the table arm chair is furniture that is used to facilitate reading and writing. This report will also be more focused on the formation of additional table expansion. Additional ways to use this table to clamp attached onto the table arm chair. Materials used to produce a table expansion are to use steel and wood. The purpose of this table expansion is designed to make the table arm chairs have enough space by using the installation. Ways and forms an attractive installation designed to make this easy to use a table expansion. Several aspects should be given full attention to ensure that this project can be carried out in line with the initial planning and be completed within the time supposed.